2017
DOI: 10.2147/ott.s136484
|View full text |Cite
|
Sign up to set email alerts
|

The HIV protease inhibitor, nelfinavir, as a novel therapeutic approach for the treatment of refractory pediatric leukemia

Abstract: PurposeRefractory pediatric leukemia remains one of the leading causes of death in children. Intensification of current chemotherapy regimens to improve the outcome in these children is often limited by the effects of drug resistance and cumulative toxicity. Hence, the search for newer agents and novel therapeutic approaches are urgently needed to formulate the next-generation early-phase clinical trials for these patients.Materials and methodsA comprehensive library of antimicrobials, including eight HIV prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Additional evidence supports the potential use of human immunodeficiency virus protease inhibitors (HIV‐PI; eg, lopinavir) as antineoplastic drugs 12 . Furthermore, the preclinical study of Meier‐Stephenson et al 13 focused on the identification of HIV‐PI‐mediated cytotoxicity in pediatric leukemia cells.…”
Section: Figurementioning
confidence: 98%
“…Additional evidence supports the potential use of human immunodeficiency virus protease inhibitors (HIV‐PI; eg, lopinavir) as antineoplastic drugs 12 . Furthermore, the preclinical study of Meier‐Stephenson et al 13 focused on the identification of HIV‐PI‐mediated cytotoxicity in pediatric leukemia cells.…”
Section: Figurementioning
confidence: 98%
“…Tian et al also reported phosphorylation of eIF2α and increased protein levels of ATF4 and CHOP in response to nelfinavir in glioblastoma cells [ 52 ]. Phosphorylation of eIF2α was also reported in nelfinavir-treated pediatric refractory leukemia cells [ 44 ]. In renal cancer cells, ER stress was shown to be induced by nelfinavir, as evidenced by the increase in GRP78, endoplasmic reticulum resident protein 44 (ERp44), and endoplasmic oxidoreductin-1-like protein α (ERO1-Lα) [ 28 ].…”
Section: Potential Mechanisms Whereby Nelfinavir Exert Its Anti-camentioning
confidence: 96%
“…Davis and colleagues reported cleavage of caspase-7 in nelfinavir-treated cisplatin-sensitive and -resistant cervical cancer cells, which corroborated similar findings in breast cancer cells [ 42 , 43 ]. In pediatric leukemia cells treated with nelfinavir, PARP cleavage was associated with the cleavage of upstream apoptosis initiator caspase-9 [ 44 ]. Liu et al observed a resensitization of doxorubicin-resistant chronic myeloid leukemia (CML) cells during co-treatment of suboptimal doses of nelfinavir with doxorubicin, which resulted in increased apoptosis associated to caspase-3 cleavage, increased proapoptotic protein Bax, and decreased anti-apoptotic protein Bcl-2 [ 45 ].…”
Section: Potential Mechanisms Whereby Nelfinavir Exert Its Anti-camentioning
confidence: 99%
See 1 more Smart Citation
“…Designing of novel cytostatic agents for leucosis treatment is a challenging task for modern pharmacology and medicine. Especially acute problem is a resistant form of decease [1][2]. A lot of modern approaches are used now for development delivery systems and screening of novel agents, e. g. virtual ligand screening [3][4].…”
mentioning
confidence: 99%